Hugo Chávez : a test for U.S. policy : a special report of the Inter-American Dialogue - Shifter, Michael (Inter-American Dialogue WashingtonUS, 2007)
Sets out a series of guidelines for U.S. policymakers that seek to put U.S. policy towards Venezuela on a more productive and coherent course.